A unique case of intravenous pyrethroid administration with poisoning - Vyom Agarwal; Prachi Dubey; Rajeev Lochan Khare; Devpriya Lakra (MRIMS Journal of Health Sciences, 2023)
Pyrethroids are widely used as insecticides at home, as part of mass anti-mosquito strategies, and in agricultural fields for control of insects. A 24-year-old female presented with a history of IV injections of around 2–3 ml of mosquito-repellent fluid (pyrethroid compounds) 2 days back. The patient complained of breathing difficulty and had normal vitals with slight derangement of laboratory parameters. On day 5 of admission, the patient complained of increased breathing difficulty with respiratory failure. The patient condition improved with oxygen and supportive care over next 5 days. The current case was unique in its route of administration being intravenous (IV), leading to more bio-exposure with less quantity of poison. No similar reports were found in the literature. There is scope for further research to throw light on the effects and toxicity of pyrethroids in plausible scenarios.